A review: Differences in halal food regulations in several countries in Asia - Muhammad Angga Abdul Aziz Guba; Muhammad Dzaki Al Munawwar (Universitas Ahmad Dahlan, 2026)
Halal regulations have become a growing issue as the Muslim population continues to grow every year. This increase in the Muslim population is accompanied by a growing demand for halal products, given that the concept of halal is a fundamental aspect of Muslim life. The differences in halal regulations across countries have not yet been fully harmonised because these standards cannot be universally standardised. The method used in this study is a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Data was obtained through the Scopus database to analyze halal regulations in several Asian countries, namely Indonesia, Malaysia, Singapore, Thailand, Japan, and South Korea. The results of the study indicate that muslim majority countries have absolute halal regulations because they are part of their citizens' rights, while non-Muslim majority countries have halal regulations that are not binding and voluntary. Each country has specific provisions related to halal product regulations. Keywords: Halal certification, Halal policy harmonization, Halal product assurance, Islamic dietary law, Global halal industry